A chattering-free sliding mode control strategy for modular high-temperature gas-cooled reactors. (November 2019) - Wang, Guoxu; Wu, Jie; Zeng, Bifan; Xu, Zhibin; Ma, Xiaoqian
Highlights: TS fuzzy models are proposed to represent the MHTGR model. An SMC controller is designed for the output power tracking control of the MHTGRs. A continuous switching function is developed to reduce the chattering phenomenon. Closed-loop system stability is guaranteed by the proposed BLSMC strategy. Effectiveness of the proposed BLSMC strategy is verified by simulation results. Abstract: Modular high-temperature gas-cooled nuclear reactor (MHTGR) is reckoned with the characteristic of reliable inherent safety, and an effective chattering-free control system is required for the load tracking control of the MHTGRs. The aim of this paper is to develop a chattering-free sliding mode controller for the power-level tracking control of the MHTGRs. Firstly, Takagi-Sugeno (TS) fuzzy control system is utilized for nonlinear modeling of the MHTGRs, and the MHTGR model is resultantly represented by TS fuzzy models. Secondly, based on the proposed TS fuzzy models, sliding mode control (SMC) is introduced for the power-level tracking control of the MHTGRs. Thirdly, a boundary layer technique that is based on a continuous switching function is used to eliminate the chattering phenomenon of SMC. Fourthly, the robustness of the proposed boundary layer based sliding mode control (BLSMC) system is also analyzed. To assess the performance and the advantages of the proposed BLSMC strategy, a conventional sliding mode control (CSMC) strategy is designed for comparisons. Simulation results show that the proposed BLSMC is well-performed for the power-level tracking control of the MHTGRs. Moreover, the proposed BLSMC strategy does not suffer from chattering.